Manajemen Kompensasi: Perspektif Global - Suhartini Suhartini (Universitas Islam Indonesia, 2004)
Companies need programs to facilitate easy movement of employees across bor¬ders. To establish a global program, the companies should first step back and make sure that the culture and belief structures in various countries will support the type of program they intend. In this millennium, international human resources (HR) will undergo a rapid trans¬formation. Strategic areas such as the integration of compensation, global staffing and busi¬ness strategy, and various issues of international HR are challenging. Expatriate compensa¬tion, for example, is presently the hottest issues in today’s discussion of international HR Compensation system should support the overall strategic intent of the organization but be customized for local condition.Keywords: Global, Compensation, Expatiate.